Extended Square-Root Covariance Filtering Algorithm for Discrete-Time Systems with Multiplicative and Additive Noises - Tsyganov, A. V.; Tsyganova, Yu. V.; Kureneva, T. N. (Lobachevskii journal of mathematics, 2022)
The paper addresses a problem of constructing extended square-root covariance filtering algorithm for discrete-time linear stochastic systems with multiplicative and additive noises. The developed algorithm is algebraically equivalent to the standard covariance filter but has the improved computational properties inherent to all square-root algorithms. The results of numerical experiments confirming the operability of the proposed algorithm are presented.